Papel dos nervos renais no diabetes mellitus experimental - Oliveira, Tales Lyra de [UNIFESP] (2018)
Introduction: Diabetes mellitus (DM) promotes increased renal sympathetic nerve activity (rSNA), autonomic imbalance, cardiovascular, metabolic and renal dysfunction. Apparently, the rSNA increases is directly associated with development and maintenance of neuropathy diabetic and autonomic nephropathy condition. Recently, there has been an important interest in clinical and experimental studies about bilateral renal denervation (BRD) procedure as a therapeutic alternative in some diseases related with renal sympathoexcitation. Aims: Protocol CEUA – UNIFESP 1787250714. Therefore, the present study evaluated the role of renal nerves on the autonomic, cardiovascular, metabolic and renal balance in the streptozotocindiabetic animal model. Methods: 8weekold Wistar rats were separated into three experimental groups: control (CTR), diabetic (DM) and denervated diabetic (DM BRD), with n=68 animals per group. DM was induced by one dose of streptozotocin (STZ; 60 mg/kg, ip) 4 weeks prior to the final experiments while the surgical BRD was performed 2 weeks before final experiments. The results were expressed as mean ± SEM and were compared by analysis of variance (ANOVA), P<0.05 was considered as the significance level. Results: DM was confirmed by body weight reduction (CTR: 351.5 ± 4.1, DM: 242.1 ± 6.7 g) and glycemia increases (CTR: 100.3 ± 3.7, DM: 509.1 ± 14.4 mg/dL). BRD significantly reduced glycemia (410.5 ± 5.8 mg/dL) and increased body weight (302.4 ± 5.7 g) in diabetic animals. DM promoted impairment of renal function such as glycosuria and albuminuria (CTR: 0,01 ± 0,001 and 0,08 ± 0,008, DM: 2.7 ± 0.19 and 0,39 ± 0,04 g/kg/24h), however BRD significantly attenuated these parameters (1,3 ± 0,19 and 0,13 ± 0,04 g/kg/24h). The heart rate (HR) was decreased in the DM animals (CTR: 352 ± 13, DM: 292 ± 11 bpm), associated with reduction of arterial baroreceptor reflex sensitivity to HR control (bradycardic response: CTR: 2.17 ± 0.06, DM: 1.92 ± 0.04 bpm/mmHg and tachycardic response: CTR: 2.55 ± 0.04, DM: 2.09 ± 0.03 bpm/mmHg). Interestingly, BRD was able to normalized HR (372 ± 23 bpm) and improved baroreflex sensitivity to the HR control (bradycardic response: 2.09 ± 0.14 and tachycardic response: 3.13 ± 0.05 bpm/mmHg) in the DM model. The rSNA was significantly increased (CTR: 82.6 ± 3.93, DM: 124.8 ± 6.45 pps), while splanchnic SNA (sSNA) was decreased in the diabetic animals (CTR: 120.5 ± 4.76, DM: 72.3 ± 5.70 pps), however BRD normalized sSNA (100.0 ± 9.23 pps) in the diabetic animals. The Na+/glucose cotransporter 2 (SGLT2) gene expression and tumor necrosis factor (TNFα) concentration were increased in the kidneys of DM group (CTR: 1.00 ± 0.24 and 233.3 ± 17.54, DM: 12.33 ± 1.25 normalized HPRT1 and 244.1 ± 12.19 pg/mL), meanwhile BRD was able to normalize (1.53 ± 0.85 normalized HPRT1 and 190.9 ± 7.53 pg/mL) these parameters.. Acutely, insulin microinjection in the rostoventrolateral medulla area (RVLM) increased mean arterial pressure (MAP; CTR: 8.7 ± 2.26, DM: 23.9 ± 19.27, DM BRD: 12.8 ± 4.25 %) and sSNA (CTR: 14.2 ± 3.50, DM: 21.2 ± 9.41, DM BRD: 17.5 ± 3.80%) only in DM groups, however, the rSNA was increased in all groups evaluated (CTR: 25.7 ± 4.62, DM: 20.6 ± 3.33%), compared to baseline means. Conclusion: Taken together, our results suggest that the renal nerves have an important role in the autonomic balance, cardiovascular, metabolic and renal function in the DM model. Furthermore, the reduction of renal SGLT2 and TNFα appears to be mechanisms involved in the improvement of these parameters (cardiovascular, autonomic, metabolic and renal) induced by BRD in the experimental DM. Cardiovascular changes in DM can be achieved by central or peripheral differential actions of insulin.